The Effect of Leadership, Work Environment and Discipline on ASN Performance with Work Motivation as an Intervening Variable in the Regional Secretariat of Padang Pariaman District - Junisa Fitri; John Veri; Yulasmi Yulasmi (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the effect of leadership style, work environment, and work discipline on the performance of State Civil Apparatus (ASN) with work motivation as an intervening variable at the Regional Secretariat of Padang Pariaman Regency. This research was motivated by suboptimal organizational performance achievements, relatively high levels of disciplinary violations, and working conditions that do not fully support ASN productivity. This study employed a quantitative approach using a survey method involving 73 ASN employees. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach to examine both direct and indirect relationships among variables. The independent variables were leadership style, work environment, and work discipline; work motivation was positioned as the intervening variable; and ASN performance was the dependent variable. The results show that leadership style, work environment, and work discipline have a significant effect on work motivation. However, leadership style does not have a significant direct effect on ASN performance, while work environment and work discipline have a positive and significant effect on performance. Work motivation also does not have a significant effect on performance and is unable to mediate the relationship between leadership style, work environment, and work discipline and ASN performance. These findings indicate that ASN performance is more strongly influenced by work discipline and work environment rather than by work motivation as an intervening variable.